Mahkamah Konstitusi dan Hak Untuk Bebas Dari Perlakuan Diskriminasi - Kurnia, Titon Slamet (Mahkamah Konstitusi Republik Indonesia, 2015)
Judicial interpretation of the right to be free from discrimination is a central issue in the practice of judicial review of the constitutionality of legislation by the MKRI. This article tries to describe and systematize this practice and then to restate the legal principles as it is stated by the MKRI into its case law. This article finds that, as a matter of principle, the MKRI adopts two main tests i.e. strict scrutiny and rational basis test to determine whether a legislation is contrary to the principle of non-discrimination